Determination of levetiracetam by GC-MS and effects of storage conditions and gastric digestive systems on drug samples - Erulas, Fatih Ahmet; Chormey, Dotse Selali; Oz, Ersoy; Bakirdere, Sezgin (Newlands Press Ltd, 2021)
Background: Epilepsy is a neurologic condition that is occurs globally and is associated with various degrees of seizures. Levetiracetam is an approved drug that is commonly used to treat seizures in juvenile epileptic patients. Accurate quantification of the drug's active compound and determining its stability in the stomach after oral administration are important tasks that must be performed. Results & methodology: Levetiracetam was extracted from drug samples and quantified by gas chromatography mass spectrometry using calibration standards. Stability of levetiracetam was studied under various storage conditions and in simulated gastric conditions. The calibration plot determined for levetiracetam showed good linearity with a coefficient of determination value of 0.9991. The limits of detection and quantification were found to be 0.004 and 0.014 mu g center dot ml(-1), respectively. The structural integrity of levetiracetam did not change within a 4-h period under the simulated gastric conditions, and no significant degradation was observed for the different storage temperatures tested. Discussion & conclusion: An accurate and sensitive quantitative method was developed for the determination of levetiracetam in drug samples. The stability of the drug active compound was monitored under various storage and gastric conditions. The levetiracetam content determined in the drug samples were within +/- 10% of the value stated on the drug labels.
Keywords: epilepsy; GC-MS; levetiracetam; simulated gastric conditions; CLINICAL PHARMACOKINETICS; ANTIEPILEPTIC DRUGS; LC METHOD; POLYTHERAPY; PERFORMANCE; ZONISAMIDE; MANAGEMENT; Biochemistry & Molecular Biology; Chemistry